GLOBAL HUMAN RESOURCE MANAGEMENT STRATEGY IN FACING MULTICULTURAL CHALLENGES IN THE DIGITAL ERA - Khaeruman, Khaeruman; Dewi, Irma Nurmala; Noor, Noorsidi Aizuddin Mat (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This study aims to investigate global human resource management (HRM) strategies for addressing multicultural challenges in the digital era. The primary focus is how multinational corporations manage cultural diversity by leveraging digital technologies. To gather information from multinational corporations in Southeast Asia the research utilized a qualitative methodology that included semi-structured interviews, document analysis, and focus group discussions. The findings indicate that incorporating digital technologies, including performance management systems and cross-cultural communication tools, markedly enhances the efficacy of HRM by promoting collaboration and transparency. These technologies also enable cross-cultural training tailored to employees' cultural backgrounds, closing cultural gaps and increasing inclusivity. Policies supporting technology use in HRM include fair training and evaluation guidelines. The findings of this study offer new viewpoints on how technology-based and adaptable human resource management strategies can assist multinational corporations in addressing multicultural challenges in the digital era